Investigating Patient Perspectives on Using eHealth Technologies for the Self-Management of Inflammatory Bowel Disease: Mixed Methods Study - Sander Hermsen; Danielle Tump; Eva Wentink; Marjolijn Duijvestein (JMIR Publications, 2024)
BackgroundInflammatory bowel disease (IBD) poses significant challenges for patients, requiring continuous monitoring and self-management to improve quality of life. ObjectiveThis study aims to investigate the viewpoints of individuals living with IBD on the use of information and communication technology (ICT) for the self-management of their condition, with a particular focus on the concept of a "smart" toilet seat as an example of ICT for IBD self-management. MethodsWe conducted an analysis of questionnaire responses obtained from 724 participants. They were encouraged to share their use cases and identify any perceived barriers associated with ICT adoption for managing their condition. To assess their responses, we used descriptive quantitative analysis, summative content analysis, and thematic qualitative analysis. We combined these results in an epistemic network analysis to look for meaningful patterns in the responses. ResultsOf the 724 participants, more than half (n=405, 55.9%) were already using various forms of ICT for IBD self-management. The primary factor influencing their use of ICT was their affinity for interacting with technology. Distinct differences emerged between individuals who were using ICT and those who were not, particularly regarding their perceived use cases and concerns. ConclusionsThis study provides valuable insights into the perspectives of individuals with IBD on the use of ICT for self-management. To facilitate wider adoption, addressing privacy concerns, ensuring data security, and establishing reliable ICT integration will be critical.